THE IMPORTANCE OF ENGLISH RIDDLES IN LINGUOCULTROLOGY - M. Yusupova (Galaxy International Interdisciplinary Research Journal, 2023)
The article provides an overview of the types of riddles and their functions as well as the importance of riddles in linguocultrology.